2020
DOI: 10.3892/ol.2020.11871
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of fibrinogen‑to‑albumin ratio in patients with gastric cancer receiving first‑line chemotherapy

Abstract: The fibrinogen-to-albumin ratio (FAR), reflecting the systemic coagulation, nutritional and inflammation status of patients, has matured into a prognostic marker for several tumor types. However, only a few studies have assessed the utility of the FAR as a prognostic indicator in patients with advanced gastric cancer (GC) receiving first-line chemotherapy. In the present study, 273 patients with advanced GC who received first-line chemotherapy between January 2014 and January 2019 at the Cancer Hospital of Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…32 Similarly, in cancer studies, FAR was a valuable marker that could predict progression-free survival and overall survival and a stronger prognostic factor than FIB and ALB alone in breast, gallbladder, renal and gastric cancer and in glioblastoma. [14][15][16]33,34 In accordance with these results, we also found that FAR had the highest OR and possessed the most predictive value in DKD and was superior to FIB and ALB. Moreover, fully adjusted spline regression showed a significant correlation of continuous FAR with DKD incidence and the risk abruptly increased when FAR exceeded 67.3mg/g.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…32 Similarly, in cancer studies, FAR was a valuable marker that could predict progression-free survival and overall survival and a stronger prognostic factor than FIB and ALB alone in breast, gallbladder, renal and gastric cancer and in glioblastoma. [14][15][16]33,34 In accordance with these results, we also found that FAR had the highest OR and possessed the most predictive value in DKD and was superior to FIB and ALB. Moreover, fully adjusted spline regression showed a significant correlation of continuous FAR with DKD incidence and the risk abruptly increased when FAR exceeded 67.3mg/g.…”
supporting
confidence: 87%
“…13 Fibrinogen to albumin ratio (FAR) is a more significant prognostic marker than each single marker itself in cancer study. [14][15][16] We speculated that FAR is also closely related to DKD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, tumor necrosis factor (TNF)- α selectively inhibits ALB gene expression and reduces ALB level ultimately ( 44 , 45 ). FAR is a more comprehensive serum marker, reflecting the inflammation and nutritional status of patients with tumors, and acting as a new promising prognostic indicator ( 46 ). The FAR and fibrinogen-prealbumin ratio (FPR) for patients with cancer were assessed in a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence showed that FARI has potential value in the early detection of cancer, and the significantly higher FARI was found in colorectal cancer patients compared with healthy controls. 15 Moreover, increasing research suggests that FARI is also a good prognostic factor for various tumors, such as gastric tumor, 16 , 17 non-small cell lung tumor, 18 gallbladder tumor, 19 prostate tumor, 20 breast tumor, 21 and hepatocellular tumor. 22 In colorectal and gallbladder cancer patients, higher FARI scores are observed in patients with unfavorable overall survival.…”
Section: Introductionmentioning
confidence: 99%